A fractal model for nuclear organization: current evidence and biological implications - Bancaud, Aurélien; Ellenberg, Jan (Nucleic acids research, 2012)
Abstract. Chromatin is a multiscale structure on which transcription, replication, recombination and repair of the genome occur.
Gesehen am 02.10.2018